Single-Cell Transcriptomic Atlas of Gingival Mucosa in Type 2 Diabetes. (December 2022) - Wang, Q.; Lin, W.; Zhou, X.; Lei, K.; Xu, R.; Zhang, X.; Xiong, Q.; Sheng, R.; Song, W.; Liu, W.; Wang, Q.; Yuan, Q.
The oral gingival barrier is a constantly stimulated and dynamic environment where homeostasis is often disrupted, resulting in inflammatory periodontal diseases. Type 2 diabetes (T2D) has been reported to be associated with gingival barrier dysfunction, but the effect and underlying mechanism are inconclusive. Herein, we performed single-cell RNA sequencing (scRNA-seq) of gingiva from leptin receptor-deficient mice ( db/db ) to examine the gingival heterogeneity in the context of T2D. Periodontal health of control mice is characterized by populations of Krt14 + -expressing epithelial cells and Col1a1 + -fibroblasts mediating immune homeostasis primarily through the enrichment of innate lymphoid cells. The db/db gingiva exhibited decreased epithelial/stromal ratio and dysfunctional barrier. We further observed stromal, particularly fibroblast immune hyperresponsiveness, linked to the recruitment of myeloid-derived cells at the db/db gingiva. Both scRNA-seq and histological analysis suggested the inflammatory signaling between fibroblasts and neutrophils as a potential driver of diabetes-induced periodontal damage. Notably, the "immune-like" stromal cells were wired toward the induction of gingival IL-17A hyperresponsiveness in db/db mice. Our work reveals that the "immune-like" fibroblasts with transcriptional diversity are involved in the innate immune homeostasis at the diabetic gingiva. It highlights a potentially significant role of these cell types in its pathogenesis.